Guided waves for structural health monitoring in composites: A review and implementation strategies. (1st February 2022) - Ricci, Fabrizio; Monaco, E.; Boffa, N.D.; Maio, L.; Memmolo, V.
Abstract: Structural Health Monitoring (SHM) systems provide a useful tool to diagnose any engineered structural system and eventual critical damage that may occur at any moment during the operational life. In the past two decades progress has been made in all the fields of SHM, from sensor technology to system integrated techniques. The common goal of any SHM system, whatever the specific application is, may be synthesized in three main points: identify structural deterioration stage, recognize its severity and evaluate the necessity to make a more detailed inspection or proceed to maintenance on condition, based on a potential hazard that may lead to a catastrophic failure. The implementation of such a system leads to making normal operations with the same safety levels but with more efficient maintenance procedures. In addition, it allows avoiding the oversizing of structural components extending the inspection and maintenance intervals. Both these results help to reduce the life-cycle cost of the specific engineered system as it is possible to perform maintenance when it is necessary, i.e. on-condition. The current state of the art about the guided waves (GW) based structural health monitoring of aerospace composite structures is reviewed in this paper, looking at the implementation of the methodologies proposed and assessed by the authors and giving an outlook on what has been done by the scientific community.